ECONOMIC POTENTIAL MAPPING ANALYSIS IN THE DISTRICT OF JEMBER - Diana Dwi Astuti (RELASI : JURNAL EKONOMI, 2017)
The paradigm change of government in the form of regional autonomy has implications for the regional authority, to explore and develop the economic potential in the development and improve the people's welfare in the region. This study aimed  to: 1) Determine the structure of the economy Jember, 2) Knowing the balance of economic resources, 3) Analyze potential sectors to be developed based on the rate of growth and productivity. The results achieved in this study are: 1) The economic structure of Jember is still dominated by agriculture sector followed by trade, hotels and restaurants, and the manufacturing sector. 2) Balance of economic resources in Jember for the agricultural sector and the reduction of mining occurred within the last 2 years (2013-2014). But the changes in the production of the agricultural sector more than the reduction in the addition in 2013 and 2014, even for the poultry production sector is not a reduction in the year 2013 and 2014. 3) The results of the analysis of LQ in the period 2009-2013 crop that became the basis are soybean, peanut, and sweet potatoes which are the basis .Horticulture: plants, large chilli and beans. Plantation crops which are the basis: kapok and nut crops. Farms that form the basis: dairy cattle, buffalo, horses, and pigs. Shift Share Based on the results, the rice plants have little competitive advantage in 31 districts. Maize, soybean, and cassava have no competitive value. Peanut and sweet potato has a very competitive value.